Pengaruh Metode Pembelajaran Problem Based Learning (PBL) terhadap Kemampuan Analisis Peserta Didik Kelas X pada Mata Pelajaran PAI di SMAN 1 Glagah Banyuwangi - Rivaldo Amirul Huda; Bahar Agus Setiawan; Dhian Wahana Putra (STIKes Ibnu Sina Ajibarang, 2025)
Discussion of education will not be separated from the core activity, namely learning. Therefore, in the teaching and learning process, various methods or learning models are delivered that aim to make it easier for students to absorb the knowledge delivered and be motivated to learn. One of the educational learning methods in Indonesia is Problem Based Learning (PBL), this method is also used in Islamic Religious Education subjects. This study aims to determine whether there is an effect of the Problem Based Learning (PBL) method on students' analytical abilities. The approach used is quantitative to collect and analyze data through numerical forms. The type of research uses a survey. This study will use data from observations, documentation, and questionnaires. The technique used for data analysis uses a simple linear regression technique so that SPSS chi square is needed to analyze it. Based on the results of the chi square analysis test on the data obtained by the researcher, it explains that the Pearson chi square value is 4.649 with a significance of 0.031 <0.05, indicating that there is a significant relationship between the PBL learning method and students' analytical abilities. The conclusion obtained based on the research conducted is that there is an influence of the Problem Based Learning method on the analytical skills of students at SMAN 1 Glagah in the PAI subject, which means Ha is accepted.